Rehabilitation trainer for upper extremities using gravity balancing - Teo, Kiat Ghee. (2011)
Rehabilitation devices have been progressively developed over the years to train and assist people who have limbs impairment in movement due to hemiparesis, arthrogryposis and spinal injuries. In order for them to regain their basic function of their limbs, passive gravity balancing technique is one of the ways to train their muscles with the weight of their limbs been removed. Passive gravity balancing has been widely used in many other areas beside rehabilitation devices. This technique has been applied on making equipoised lamp, tower cranes and kitchen cabinets.